Wild Life Management - Chaturvedi, M. D. (Indian Forester, 1968)
The wide range of climatic variations of the Indian sub-continent, its extent and diverse physical features have given rise to a rich and varied fauna consisting of about 400 species of mammals, 1,100 species of birds and 350 species of reptiles. It is the forest of this region that sustains wild life and determines its character and colouration, size and distribution. Protected by religious sentiments and insulated by inaccessible forest cover through the ages, the wild life of the country was suddenly exposed to attacks on two fronts with the advent of the British on the scene. Not only had animals to defend themselves against trigger-happy sportsmen of those days, but also against the ever diminishing forest cover which gave them shelter and sustenance. Unable to fend for themselves quite a few species became extinct; and, many more were driven to the verge of extinction. Control on wanton destruction of wild life was sought through legislation at the turn of the century. The gap between legislation and its implementation has been bridged to some extent by the creation of a healthy public opinion through non-official organizations. Inspired by the action taken by European powers for the preservation of wild life in Africa, and moved by the International Union for the Conservation of Nature (I.U.C.N.), Independent India set up in 1952 the Indian Board for Wild Life with its counterparts in the States. The need of the hour is wise land use in the context of unbridled encroachment of cultivation. What is needed is not only the preservation of wild life but also the preservation of the forest that provides sustenance and cover to its sprightly and colourful denizens.